The Comparison of The Subfoveal Choroidal Thickness Measurements Obtained Using the Inverse and Straight Images of Spectral Domain Optical Coherence Tomography in Healthy Subjects (Annals of Medical Research, 2021)
None
Keywords: Optical Coherence Tomography; Straight Image; Inverse Image; Choroidal Thickness; Healthy Subjects.